Advances in laparoscopic surgery in urology - Rassweiler, Jens; Teber, Dogu (Nature reviews. Urology, 2016)
Laparoscopic techniques are subject to continuous change and benefit from new developments. Robot-assisted surgery has substantially revolutionized laparoscopy, increasing its distribution; however, it is associated with considerable costs. In this Review, Rassweiler and Teber discuss technical improvements, developing technologies and speculate on the future of minimally invasive surgery and laparoscopy in urology.